Emerging trends in mobile technology: a 5g perspective - Sourav Mohanty, Mr; Chandrabhanu Das, Dr (International Journal of Engineering and Technology, 2018)
Fifth Generation technology is proposed to be launched in India around 2020 and it is estimated to resolve the technological barriers to 4G technologies. The increased use of digital technology in all spheres of life has necessitated the use of efficient and reliable mobile communications. 5G has advantage over 4G in optimum use of technology. The paper discusses the legal and regulatory issues, feasibility in rural areas and architectural framework. The article highlights about the proposed 5G Architecture requirements, need of 5G, its launch in India and other suitable innovative technology that will suffice 5G operations smoothly. The article is basically written as a twofold. Extensive literature reviews on past studies of 5G and its assumed to be architectural features in near future are discussed based on current technological trends, innovations. Moreover, it is a descriptive and conceptual perspective. It is purely based on secondary data available in Internet and various other topic related research article publications. Lack of empirical data and 5G is not officially released worldwide, but except in some countries, it is given on a basis of beta testing unit. Practically 5G Mobile Technology will be launched in India around 2020 and only after that, comments would be taken into account. This paper discusses vividly about 5G penetration in rural India and its use in Big Data Analysis as small-scale cells called Heterogeneous networks. Â